The Analysis of Village Fund Management in Juuh Village, Tebing Tinggi District, Balangan Regency - Ridhawati, Rakhmi; Putri , Winda Agusntina; Nurhayati , Netty Nurhayati; Yuliastina, Mellani (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
This study aims to analyze on how the Management of Village Fund in Juuh Village, Tebing Tinggi Subdistrict, Balangan Regency in 2019 according to Permendagri No. 20 of 2018. Village Funds are one of the government accountability to increase the development in rural area. The source of Village Fund is from State Budget Revenue and Expenditures which allocated for Transferred village through Budget Income and District Area Spending and used for maintaining governance finance, development on executin, community construction, and society empowerment. This study was held in Juuh Village, Tebing Tinggi Subdistrict, Balangan Regency. This study uses qualitative method with techniques for data collection as interview, observation, and documentation. Informants on this research consist of the Head of Juuh Village and its apparatus with the total of seven people. The results study shows that there are corresponding with Permendagri No. 8 of 2018 concerning Management Village Finance at implementation and administration level. Meanwhile at planning, reporting, and accountability level there is no corresponding with Permendagri No. 20 of 2018 concerning Village Financial Management.